Are there conditions that can predict when an M&A works? The case of Italian listed banks - Roberta Arbolino; Raffaele Boffardi; Konstantinos Kounetas; Ugo Marani; Oreste Napolitano (Economies, 2023)
This paper investigates the impact in the short/medium term of M&As made by 14 Italian banks quoted on the stock exchange for the period 1999-2016. After dividing the banks into two groups by size and degree of internationalisation, we sought to ascertain whether different initial conditions produce different final effects. Based on three assumptions, supported by three separate econometric approaches, our empirical analysis shows that the stronger banks increased their competitiveness while the weaker banks did not achieve the same results since they were motivated to grow 'by desperation.
Keywords: 330; M&A; bank lending; listed banks; bank shocks; Italy